Pelatihan Pembuatan Slide Presentasi Power Point Secara Interaktif - Sri Yanna; Ristawati; Mirza; Chaeroen Niesa (Aceh Journal of Community Engagement (AJCE), 2022)
Improving skills is one way to improve the quality of human resources. One form of skill that may be needed by everyone is presentation technique. Both in business activities, education, and organizations. Interesting presentation techniques with the help of Power Point will be able to increase the audience's interest in the ideas presented. This presentation technique training is intended for teachers of SMA Negeri 1 Jeumpa. The methods used in this community service are lectures, direct practice with computers and with direct assistance so that participants can be faster and focus on making interesting presentations. The implementation of this community service can be said to be successful, because of the suitability of the material to the needs of the participants, the positive response from the participants and the wishes of the participants where the training took place to be developed with other topics. which can improve the standard of living of the surrounding communit